Reaching Chinese in the World—Christian Literature in Post-war Hong Kong - Zhou, Yun (2025)
During the Cold War, various political forces sought to shape the mindset of the Chinese diaspora. One understudied cultural influence that played an important role in reaching overseas Chinese was Chinese Christian literature. Focusing on Dengta (Lighthouse, 1956-1967), the first Chinese Christian magazine aimed at non-Christian communities in the diaspora, this study examines how the magazine developed an evangelical discourse that engaged with the cultural and spiritual identities of the Chinese diaspora amid political and ideological conflicts. Published in Hong Kong, which emerged as a hub for Chinese Christian literature in the post-war period, the magazine reflects a pivotal shift in Chinese Christian publishing: the start of a global movement aimed at evangelizing overseas Chinese. To appeal to the diaspora, Dengta adopted an ethnic and cultural rhetoric of Chineseness and presented Christian ideals in a context that resonated with the experiences of the Chinese diaspora. I argue that the Chineseness promoted by Dengta helped construct a transregional and transnational sense of belonging for overseas Chinese by framing a blend of traditional Chinese culture and modern knowledge within a Christian cosmic worldview. This study foregrounds the evangelical efforts of Christian literary workers to shape the diasporic experience amid the political tensions of the Cold War.
Keywords: Chineseness; Christian Literature; Dengta; Hong Kong; Diaspora; the Cold War